2010
DOI: 10.1016/j.mce.2009.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone-binding globulin gene expression in the liver: Drugs and the metabolic syndrome

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. decrease SHBG expression by inducing lipogenesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 88 publications
6
90
0
1
Order By: Relevance
“…In vitro studies showed that mitotane increases the synthesis of steroid binding protein (26,27). In our study, SHBG was markedly increased, whereas in males free T was decreased and LH was increased.…”
Section: Hormonal Parameterssupporting
confidence: 48%
“…In vitro studies showed that mitotane increases the synthesis of steroid binding protein (26,27). In our study, SHBG was markedly increased, whereas in males free T was decreased and LH was increased.…”
Section: Hormonal Parameterssupporting
confidence: 48%
“…The mechanism underlying the relationship between SHBG and PAD is not completely understood (32) . SHBG is produced by liver and is down-regulated by insulin levels (32)(33)(34) .…”
Section: Shbg and Padmentioning
confidence: 99%
“…SHBG is produced by liver and is down-regulated by insulin levels (32)(33)(34) . Along with the well-known role of transport protein SHBG is also involved in other independent functions (32,(35)(36) .…”
Section: Shbg and Padmentioning
confidence: 99%
See 2 more Smart Citations